Peran Pekerja Sosial dalam Mengembalikan Fungsi Sosial Anak Panti pada LKSA An-Nur - Ginting, Ridho Novtiaziz; Asbi, Erni Asneli (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to determine the role of social workers in restoring the social functioning of orphanage children at LKSA An-Nur. The stages of intervention carried out by social workers in restoring the client's social functioning consist of 6 stages, namely, Intake contract, Assessment, Planning, Intervention, Evaluation, Termination The results showed that the role of social workers in restoring children's functioning still experienced many obstacles, especially differences in perception between social workers and social institutions. This article provides important implications for social workers and social institutions to collaborate with each other in providing social services to clients and also provide varied interventions to clients.